PENGARUH METODE SAINTE LAGUE DALAM PENENTUAN ALOKASI KURSI DI DPR/DPRD PROVINSI DAN DPRD KABUPATEN/KOTA - Yakub, Sandra Leoni Prakasa; Fathin, Siti Labiba (Jurnal Keadilan Pemilu, 2023)
The main problem of this research is the use of the Sainte Lague vote conversion method in electing members of the House of Representatives (DPR)/Regional Legislative Council (DPRD) Province or the Regional Legislative Council (DPRD) Regency/City. The application of the sainte lague method is contained in Article 415 paragraphs (2) and (3) of Law Number 7 of 2017 concerning general elections. The approach method used is normative juridical, with secondary data collection methods in the form of primary, secondary, and tertiary legal materials. The results of the study show: first, in the 1999, 2004, 2009, and 2014 elections, Indonesia used the hare vote conversion method, and in the 2019 elections, Indonesia used the sainte lague vote conversion method; second, the application of the vote conversion method will actually injure human rights, the principle of popular sovereignty, the concept of democracy, and the purpose of elections. To create a democratic electoral system, the author proposes abolishing the vote conversion method and calculating the winners of the DPR/DPRD Provincial and DPRD Regency/City elections based on the majority of votes they receive.